2012 IEEE International Conference on Multimedia and Expo 2012
DOI: 10.1109/icme.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Motion Vectors Merging: Low Complexity Prediction Unit Decision Heuristic for the Inter-prediction of HEVC Encoders

Abstract: This paper presents the Motion Vectors Merging (MVM) heuristic, which is a method to reduce the HEVC inter-prediction complexity targeting the PU partition size decision. In the HM test model of the emerging HEVC standard, computational complexity is mostly concentrated in the inter-frame prediction step (up to 96% of the total encoder execution time, considering common test conditions). The goal of this work is to avoid several Motion Estimation (ME) calls during the PU inter-prediction decision in order to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Fig.7 and Fig. 8 demonstrate rate-distortion performances and encoding time performances with respect to HM12.0 reference software [10] and MVM based approach discussed in Sampaio et al [5] for two CIF sequences and Fig. 9 shows the same performance graphs for a HD sequence.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Fig.7 and Fig. 8 demonstrate rate-distortion performances and encoding time performances with respect to HM12.0 reference software [10] and MVM based approach discussed in Sampaio et al [5] for two CIF sequences and Fig. 9 shows the same performance graphs for a HD sequence.…”
Section: Resultsmentioning
confidence: 97%
“…Considering the partitioning behavior of CUs with respect to inter prediction, it can be observed that blocks with similar motion tend to utilize large CUs while blocks with complex motion utilize smaller CUs [5][6][8] [9]. Fig.…”
Section: Proposed Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this comes at the expense of computational complexity and poses a challenge to hardware design and implementation. Profiling shows that ME unit reaches up to 96% of the encoding time [9], and SAD unit takes the majority of this complexity, especially in the case of CTB size 64x64, which can be divided into more than 600 PBs with different sizes. Sseveral hardware architectures were proposed to speed up the SAD unit for ME in HEVC [10][11][12].…”
Section: Related Workmentioning
confidence: 99%
“…Inter frame prediction alone consumes from 60% to 96% of the total encoding time [26]. In [13], inter prediction is shown to consume 84% of the encoding time while only 3% is taken by intra prediction for High Definition (HD) sequences.…”
Section: Introductionmentioning
confidence: 99%